Multichannel Plating Unit for High-Throughput Plating of Cell Cultures. (August 2002) - Hamilton, C.M.; Anderson, M.; Lape, J.; Creech, E.; Woessner, J.
High-throughput genomic approaches to gene function or target identification have led to the development and implementation of the 96-well format for many standard molecular biology manipulations. The apparatus described here, a Multichannel Plating Unit, is designed to plate out individual cultures efficiently from standard 96-well culture blocks. Following transformation, aliquots of culture are loaded onto sterile beads that are rolled along individual channels of agar media. After the beads traverse the channel, they drop into the exit alley for disposal via an exit pore. The apparatus presented has 12 individual lanes, and the spacing is compatible with a standard 12-channel pipettor. Thus, the unit allows for the rapid plating of 12 individual cultures at a time. For one 96-well block of transformants, this method reduces the labeling and plating effort from 96 culture dishes that are spread individually to eight multichannel plates. The savings in time, materials, and storage space is significant.